A new species of Raorchestes (Amphibia: Anura: Rhacophoridae) from mid-elevation evergreen forests of the southern Western Ghats, India - Seshadri, Kadaba Shamanna; Gururaja, Kotambylu Vasudeva; Aravind, Neelavara Anantharam (Zootaxa, 2012)
A new species of the shrub frog genus Raorchestes Biju, Souche, Dubois, Dutta and Bossuyt is described as Raorchesteskakachi sp. nov. from Agastyamalai hill region in the southern Western Ghats, India. The small sized Raorchestes (male:24.7–25.8 mm, n = 3 and female: 24.3–34.1 mm, n = 3) is distinguished from all other known congeners by the followingsuite of characters. Snout oval in dorsal view; tympanum indistinct; head wider than long; moderate webbing in feet;colour on dorsum varying from ivory to brown, blotches of dark brown on flanks, brown mottling on throat reducing to-wards vent; inner and outer surface of thigh, inner surface of shank and inner surface of tarsus with a distinct dark brownhorizontal band which extends upto first three toes on upper surface. A detailed description, advertisement call features, ecology, natural history notes and comparison with closely related species are provided for the new species.